2015
DOI: 10.1155/2015/831569
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Sleep‐Disordered Breathing and Magnetic Resonance Imaging Findings in a Pediatric Cohort with Chiari 1 Malformation

Abstract: A direct relationship between the degree of cerebellar tonsillar herniation and obstructive sleep apnea was demonstrated. However, further prospective studies that include neurophysiological assessment are needed to further translate the central nervous system imaging findings to predict the presence of SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…Innate bias, however, is inevitable in an in-hospital cohort. Sleep apnea and feeding problems are reported to be more common in pediatric patients, although other clinical manifestations appear to be similar in different age groups (6). As previously reported, the most common presenting symptom of CM-I is headache (4), which is consistent with the current findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Innate bias, however, is inevitable in an in-hospital cohort. Sleep apnea and feeding problems are reported to be more common in pediatric patients, although other clinical manifestations appear to be similar in different age groups (6). As previously reported, the most common presenting symptom of CM-I is headache (4), which is consistent with the current findings.…”
Section: Discussionsupporting
confidence: 91%
“…With the advent of magnetic resonance imaging (MRI), however, the number of pediatric patients diagnosed with CM-I is increasing (4). Previous studies have described the clinical features of CM-I in pediatric populations (2,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Of those with isolated OSA, nearly one‐half had abnormal brain MRI findings. Although CSA is traditionally regarded as the most frequent respiratory complication of brain abnormalities, more recent literature has shown that neuroanatomical malformations can contribute to OSA in the absence of adenotonsillar hypertrophy . Likewise, our findings reinforce the importance of obtaining a brain MRI to detect potential neuroanatomical causes of OSA.…”
Section: Discussionsupporting
confidence: 82%
“…In children, isolated OSA in the absence of adenotonsillar hypertrophy, persistent OSA following AT, and OSA with coexisting significant CSA pose a dilemma for clinicians. Although previous studies have shown that underlying neuroanatomical abnormalities can contribute to persistent isolated OSA in the absence of adenotonsillar hypertrophy, CSA, and NH, the present study is the first descriptive study of brain MRI findings following a PSG diagnosis of a sleep disorder to determine outcomes for brain imaging in a heterogeneous population consisting of nonsyndromic and syndromic children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation